Improvements to CPCES - Zhang, Xiaodi; Grastien, Alban (Proceedings of the International Symposium on Combinatorial Search, 2023)
This paper introduces three improvements to the conformant planner CPCES, which continuously searches candidate plans and counter-examples against the current candidate plan until a valid plan (no counter-example exists) is found. First, we identify and merge equivalent PDDL facts to accelerate candidate plan generation. Second, we warm-start CPCES by generating multiple carefully selected counter-examples at the beginning of the procedure, which reduces the number of calls to the classical planner. Third, we investigate the use Fast Downward (FD) as the candidate plan generator; in particular, we propose an incremental procedure to generate the SAS+ file used by FD. Our experimental results show significant improvements for each technique.